Sobre a permanência da Filosofia na escola e sua relação com o mundo tecnológico - Rissatto, Marcelo Artur (2021)
This work intends to locate the role of philosophy in a world completely transformed (and in transformation) of the technological age, especially in what concerns the new information technologies. With this purpose, at first, we tried to demonstrate that the history of humanity is essentially the history of technique, seeking to establish a parallel of human development from the evolution of technique, to Greek techné and, later, to modern technology. The aim is to establish the validity of the idea that a computer revolution is currently underway that is modifying the human world in order to inaugurate a new anthropological moment. Based on that, the work investigates the main characteristics of this “new human world” formed from information technologies, exploring the concept of “virtuality” to determine the existence of what the philosopher Pierre Lévy called cyberspace and cyberculture. In a second step, this work will investigate how philosophy relates to technique and technological development, seeking to present the arguments of those philosophers who view technological development with suspicion, while presenting the prejudice that points to philosophy as useless within a technological world. That done, it is intended to demonstrate that such a view is based on a misinterpretation of the relationship between technology and humans, based on a mechanism that can be overcome. For this purpose, the arguments of John Searle and Pierre Lévy are presented, to demonstrate that technology will not supplant humanity due to the fact that a machine cannot think. Finally, it is intended to present a defense of the teaching of philosophy as a discipline of basic education, demonstrating that not only does philosophy have a place in the technological world, but that philosophers are occupying decisive positions in this future ahead.